The Many Alternative Faces of Macrophage Activation - Hume, David A. (Frontiers in Immunology, 2015)
Monocytes and macrophages provide the first line of defense against pathogens. They also initiate acquired immunity by processing and presenting antigens and provide the downstream effector functions. In large gene expression datasets from multiple cells and tissues, it is possible to identify sets of genes that are co-regulated with the transcription factors that regulate them. In macrophages, they include lineage-specific genes, interferon-responsive genes, early inflammatory genes, and those associated with endocytosis. Macrophages enter tissues and alter their function to deal with a wide range of challenges related to development and organogenesis, tissue injury, malignancy, sterile or pathogenic inflammatory stimuli. These stimuli alter gene expression to produce “activated macrophages” that are better equipped to eliminate the cause of their influx, and to restore homeostasis. Activation or polarization states of macrophages have been classified as “classical” and “alternative” or M1 and M2. These proposed states of cells are not supported by large-scale transcriptomic data, including macrophage-associated signatures from large cancer tissue datasets, where the supposed markers do not correlate with other. Individual macrophage cells differ markedly from each other, and change their functions in response to doses and combinations of agonists and time. The most studied macrophage activation response is the transcriptional cascade initiated by the TLR4 agonist lipopolysaccharide (LPS). This response is reviewed herein. The network architecture is conserved across species, but many of the target genes evolve rapidly and differ between mouse and human. There is also considerable divergence in the sets of target genes between mouse strains, between individuals and in other species such as pigs. The data and publication deluge related to macrophage activation requires the development of new analytical tools, and ways of presenting information in an accessible